European Society for the Study of Coeliac Disease (ESsCD) guideline for coeliac disease and other gluten-related disorders. Issue 5 (June 2019) - Al-Toma, Abdulbaqi; Volta, Umberto; Auricchio, Renata; Castillejo, Gemma; Sanders, David S; Cellier, Christophe; Mulder, Chris J; Lundin, Knut E A
This guideline presents recommendations for the management of coeliac disease (CD) and other gluten-related disorders both in adults and children. There has been a substantial increase in the prevalence of CD over the last 50 years and many patients remain undiagnosed. Diagnostic testing, including serology and biopsy, should be performed on a gluten-containing diet. The diagnosis of CD is based on a combination of clinical, serological and histopathological data. In a group of children the diagnosis may be made without biopsy if strict criteria are available. The treatment for CD is primarily a gluten-free diet (GFD), which requires significant patient education, motivation and follow-up. Slow-responsiveness occurs frequently, particularly in those diagnosed in adulthood. Persistent or recurring symptoms necessitate a review of the original diagnosis, exclude alternative diagnoses, confirm dietary adherence (dietary review and serology) and follow-up biopsy. In addition, evaluation to exclude complications of CD, such as refractory CD or lymphoma, should be performed. The guideline also deals with other gluten-related disorders, such as dermatitis herpetiformis, which is a cutaneous manifestation of CD characterized by granular IgA deposits in the dermal papillae. The skin lesions clear with gluten withdrawal. Also, less well-defined conditions such as non-coeliac gluten sensitivity (NCGS) and gluten-sensitive neurological manifestations, such as ataxia, have been addressed. Newer therapeutic modalities for CD are being studied in clinical trials but are not yet approved for use in practice.